Surgical Management of Vascular Anomalies in Extremities: A Case Series - Permatasari, Gita; Tua, Ivan Joalsen Mangara (Journal of Indonesia Vascular Access, 2024)
Introduction: Vascular malformations and vascular tumors are the two categories of vascular anomalies in the ISSVA categorization system. Although surgery has historically been the primary method of treating vascular abnormalities, it is increasingly frequently combined with other procedures. Thus, the purpose of this study is to outline the several surgical approaches for treating vascular abnormalities in the extremities. Case: In this series study revealed six patiens with vascular malformation who underwent surgical treatment. The locations of the lession more frequently in lower extremity than upper extremity. Few cases need reconstrution using flap or skin graft. Three cases were recurrent hemangiomas which underwent surgical excision before this study. In the follow-up, there were no signs of tumor reccurence after the secondary surgical excision. Four patients had combined therapy with scleroting agent.  Conclusion: Hence, surgical management is constantly the treatment of coice for vascular anomalies. Combined therapy with scleroting agent may use in the case which unable to do expansive excision.